2021
DOI: 10.1016/j.jneuroim.2021.577658
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of COVID-19: A comprehensive literature review and discussion of mechanisms

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 130 publications
(235 reference statements)
1
50
0
Order By: Relevance
“…A recent review and critical discussion of SARS-CoV-2-associated neurological, cognitive and psychiatric deficits presents a multi-faceted profile of putative mechanisms underlying the neurotropic/neuroinvasive potential of the virus (32). Complementary in vivo, in vitro and neuropathological studies suggest convergent and potentially synergistic strategies used by SARS-CoV-2 for neuroinvasion, infection, and replication within CNS neurons and astrocytes with subsequent cellular and tissue damage linked to chronic neurological dysfunction (33)(34)(35).…”
Section: Infection Of the Brain: Chronicity Neuronal Activity And Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review and critical discussion of SARS-CoV-2-associated neurological, cognitive and psychiatric deficits presents a multi-faceted profile of putative mechanisms underlying the neurotropic/neuroinvasive potential of the virus (32). Complementary in vivo, in vitro and neuropathological studies suggest convergent and potentially synergistic strategies used by SARS-CoV-2 for neuroinvasion, infection, and replication within CNS neurons and astrocytes with subsequent cellular and tissue damage linked to chronic neurological dysfunction (33)(34)(35).…”
Section: Infection Of the Brain: Chronicity Neuronal Activity And Cognitionmentioning
confidence: 99%
“…Overall, the authors provided evidence for the neuroinvasive capacity of SARS-CoV-2 in an apparent ACE2-dependent mechanism. In contrast, the lack of consistency of recent in vitro and in vivo datasets supporting a direct neuroinvasion by SARS-CoV-2, suggests that a virus-induced loss of BBB integrity with heightened CNS influx of inflammatory molecules is the likely culprit in long COVID-associated neurological and psychiatric disorders ( 32 ). Accordingly, these long-term debilitating neurological sequelae appear to be functionally linked to chronic inflammatory conditions within CNS structures and potential key entry points, such as choroid plexa ( 18 ), via chronically activated microglia.…”
Section: Infection Of the Brain: Chronicity Neuronal Activity And Cognitionmentioning
confidence: 99%
“…Solid epidemiological data have shown that patients with COVID-19 present with frequent and diverse neurological symptoms regardless of the level of clinical severity [12][13][14], and these symptoms occurred more frequently in persons with more severe systemic presentations [15]. Currently, hospitalized patients represent a minority of COVID-19-infected cases, due to both the lack of risk factors for severe disease in many sectors of the general population and the introduction of the vaccine for SARS-CoV-2; however, non-hospitalized patients may also develop sequelae following infection, including neurological symptoms [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological disturbances such as myopathy, disorientation/encephalopathy, neuropathy, stroke, seizures, cerebral hemorrhage, cerebral venous thrombosis, and subarachnoid hemorrhage are considered neurological complications of COVID-19 [14].…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…Infection by SARS-CoV-2 has been shown to lead to multiple neurological manifestations [ 3 ], with the most common being dizziness, headache, anosmia, and ageusia [ 4 ]. However, some isolated cases of GBS have also been reported worldwide [ 5 ].…”
Section: Discussionmentioning
confidence: 99%